Loss of FKBP5 Affects Neuron Synaptic Plasticity: An Electrophysiology Insight. (15th March 2019) - Qiu, Bin; Xu, Yuxue; Wang, Jun; Liu, Ming; Dou, Longyu; Deng, Ran; Wang, Chao; Williams, Kent E.; Stewart, Robert B.; Xie, Zhongwen; Ren, Wei; Zhao, Zhenwen; et al.
Graphical abstract: Highlights: LTP reduced in Fkbp5 KO male mice relative to WT, indicating altered neuron function. Expression of excitatory glutamate receptors (NMDAR1, NMDAR2B, and AMPAR) and mEPSC frequency reduced in KO. Increased GABA expression and mIPSC frequency in KO hippocampus. Male Fkbp5 KO mice display low saccharin intake and higher immobility. Abstract: FKBP5 (FKBP51) is a glucocorticoid receptor (GR) binding protein, which acts as a co-chaperone of heat shock protein 90 (HSP90) and negatively regulates GR. Its association with mental disorders has been identified, but its function in disease development is largely unknown. Long-term potentiation (LTP) is a functional measurement of neuronal connection and communication, and is considered one of the major cellular mechanisms that underlies learning and memory, and is disrupted in many mental diseases. In this study, a reduction in LTP in Fkbp5 knockout (KO) mice was observed when compared to WT mice, which correlated with changes to the glutamatergic and GABAergic signaling pathways. The frequency of mEPSCs was decreased in KO hippocampus, indicating a decrease in excitatory synaptic activity. While no differences were found in levels of glutamate between KO and WT, a reduction was observed in the expression of excitatory glutamate receptors (NMDAR1, NMDAR2B and AMPAR), which initiate and maintain LTP. The expression of the inhibitory neurotransmitter GABA was found to be enhanced in Fkbp5 KO hippocampus. Further investigation suggested that increased expression of GAD65, but not GAD67, accounted for this increase. Additionally, a functional GABAergic alteration was observed in the form of increased mIPSC frequency in the KO hippocampus, indicating an increase in presynaptic GABA release. Our findings uncover a novel role for Fkbp5 in neuronal synaptic plasticity and highlight the value of Fkbp5 KO as a model for studying its role in neurological function and disease development.